Online Communication Behaviors in Covid-19 Pandemic: Exploring the Influence of Internal Public Relations Practices and Employee Organization Relationships - Alsharairi, Ahmad; Jamal, Jamilah; Yusof, Norhafezah (South Asian Journal of Social Sciences and Humanities, 2022)
Health organizations are increasingly looking for effective strategies for interaction and for maintaining long-term and mutually beneficial relationships with their employees. The growth of digital environments in particular, during Covid-19 Pandemic has offered a fresh avenue for employees to communicate with external publics through social media in crisis. During Covid 19 Pandemic, major healthcare sectors have been deeply impacted, nurses in Jordanian hospitals are suffering from a great challenge from their top management due to weak transparent communication and during a crisis, many reports nurses indicate that their organizations or leaders do not promote communication or the sharing of information and ideas. This represents the problem in which nurses do not have faith in the tolerance or benevolence of their managers. Jordanian hospitals reputation is increasingly questioned during the COVID-19 crisis (World Health Organization, 2020). This crisis involving Jordanian hospitals has resulted in declining nurses trust in the health care sector and their nurses more adversaries by sharing negative information about their hospitals on social media. ultimately turned into emergence of crisis communication in the healthcare sector and the decline of nurses’ support for their management. If the current trend persists, may likely lead to an unfavorable reputation for future of health care sector in Jordan. Taking this into consideration, the current paper expects to further explore and comprehend, employee’s online communication behaviors during Covid-19 Pandemic in Jordanian public hospitals. This conceptual paper debates the antecedents that contribute across Jordanian nurses’ motivation in online communication behaviors based on a comprehensive literature review. In particular, the paper elaborates on the proposed relationships between transparent communication, symmetrical communication employee organization relationships, and online communication behaviors. Based on the extended discussions of the proposed relationships, the paper also provides an effective framework for future public relations scholarship of understanding employees’ communication behaviors in online sitting. Therefore, identifying antecedents of employee communication behaviors is a very pertinent, timely initiative to restore employees trust and obtain their support during a crisis. This can be done by utilizing a specific mechanism to decrease threats in the public health sector and create positive results, such as positive employee communication behaviors.